Handbook of numerical methods for the solution of algebraic and transcendental equations - Zaguskin, V. L. (Vladimir Lvovich) (Pergamon Press, 1961)
The solution of algebraic and transcendental equations is one of the essential problems of applied analysis which arises in many and different departments of physics, mechanics, engineering, and science in general. Much attention in existing textbooks is devoted to the explanation of practical methods for the solution of equations, but in Russian education literature no special textbook exists which gives no only a summary of the classical methods, but including specially selected materials, developed in recent decades, and have been practically applied. This book is intended to fill the gap, while providing a textbook, of reference type, for a wide range of readers.